Predation of Ctenosaura pectinata (Squamata: Iguanidae) by Lynx rufus (Carnivora: Felidae) in the State of Michoacán de Ocampo, Mexico - Charre-Medellin, Juan; Monterrubio-Rico, Tiberio C.; Gómez-Cárdenas, Eliazin; Alvarado, María del Socorro; Barragán-López, Esteban; Torres-Villa, Rogelia (Mammalogy Notes, 2020)
The wild cat or red lynx (Lynx rufus), is a medium-sized feline with a wide distribution in Mexico and North America, for which its diet has been documented throughout its entire range, being lagomorphs and rodents. its main prey. Through camera monitoring, the first evidence of the presence of the black iguana (Ctenosaura pectinata) in the diet of the wild cat is documented. In addition to the presence of wild cats, five feline species were recorded; cougar (Puma concolor), jaguarundi (Herpailurus yagouaroundi), tigrillo (Lepoardus wiedii), ocelot (Leopardus pardalis) and jaguar (Panthera onca). Subsequent studies must evaluate the overlap of niche and preference of feeding habits of the cats present in this region of the country, where the six species of cats that live in Mexico coexist. El gato montés o lince rojo (Lynx rufus), es un felino de talla mediana con una amplia distribución en México y Norteamérica, para el cual se ha documentado su dieta a lo largo de toda su área de distribución, siendo los lagomorfos y los roedores sus principales presas. Mediante un monitoreo con cámaras trampa, se documenta la primera evidencia de la presencia de la iguana negra (Ctenosaura pectinata) en la dieta del gato montés. Además de la presencia de gato montés se registraron cinco especies de felinos; puma (Puma concolor), jaguarundi (Herpailurus yagouaroundi), tigrillo (Lepoardus wiedii), ocelote (Leopardus pardalis) y jaguar (Panthera onca). Estudios posteriores, deben evaluar el traslape de nicho y preferencia de hábitos alimenticios de los felinos presentes en esta región del pais, donde coexisten las seis especies de felinos que habitan en México.